PENGARUH MINAT BERWIRAUSAHA, MOTIVASI DAN KREATIVITAS TERHADAP KEBERHASILAN USAHA PELAKU USAHA DI DESA PEGADUNGAN - Widyasmara Sukramayun, I Putu Dicky; Suardika, I Ketut (Jurnal Daya Saing, 2024)
This research aims to determine the influence of entrepreneurial interest, motivation and creativity on the business success of business actors in Pegadungan Village. This research aims to (1) To determine the influence of interest in entrepreneurship on business actors in Pegadungan Village, (2) To determine the influence of motivation on business actors in Pegadungan Village and (3) To determine the influence of creativity on business actors in Pegadungan Village. The method used in this research is quantitative. The data collection techniques used are documentation and questionnaires. The sample used in this research was 121 people or all business actors in Pegadungan Village. The data analysis technique used is multiple linear regression analysis. The research results show that: (1) Interest in Entrepreneurship has a positive and significant effect on Business Success. (2) Motivation has a positive and significant effect on business success. (3) Creativity has a positive and significant effect on business success